Textbook of gastrointestinal radiology - Gore Richard M. (Philadelphia Saunders/Elsevier, 2008)
The third edition of this two-volume set features new chapters on CT colonography, PET/CT, MRCP, 3D applications of MDCT, CT enteroclysis, MR enteroclysis, MR colonography, MR angiography, CT angiography, and video capsule endoscopy. All chapters have been thoroughly updated to reflect the newest techniques in gastrointestinal imaging. As in the last edition, the spectrum of diseases of the solid and hollow viscera of the abdomen and pelvis in the adult and pediatric patient is comprehensively reviewed. Diagnostic imaging algorithms and differential diagnoses of imaging features are emphasized.
Keywords: Gastrointestinal system -- Radiography; Gastrointestinal Diseases -- diagnosis; Diagnostic Imaging -- methods